Determinação de etanol em bebidas alcoólicas empregando entalpimetria no infravermelho - Oliveira, Alessandra Stangherlin (2016)
Methods used for ethanol determination in alcoholic beverages require a previous step of distillation, presenting some limitations as long time and high energy consumption as well as the use of high amount of sample for analysis. The infrared thermography enable monitoring temperature distribution of an object. This technique can be combined with the enthalpimetric analysis, monitoring the temperature of a chemical reaction by direct or indirect form. Considering these characteristics, a new approach is proposed in this work in order to perform a simple and fast analysis without the use of toxic reagents and avoiding sample preparation, by using thermal infrared enthalpimetry (TIE). In this sense, microplate devices with 24 wells as reactors and a multichannel pipette for reagents addition were used with temperature monitoring by means of an infrared camera. In this way, a study to determine the alcoholic content of distillates and fermented beverages was performed, using the temperature variation from the heat of dilution. In order to evaluate the proposed method, a previous optimization was performed evaluating some parameters as the total volume, the dispensing speed, the stirring speed and the proportion between solutions. The results obtained by the proposed TIE method were in agreement with those obtained by the conventional method used to determine the alcoholic content (AOAC, 942.06), ranging from 99.4 to 100.9 % and 97.7 to 105.0% for distillated and fermented beverages, respectively. In addition, this method provided a high sample throughput (up to 480 samples in one hour). In this sense, a good performance of the proposed method was observed, presenting a potential to be applied in routine analysis due its simplicity and rapidity, being an important tool for ethanol determination in alcoholic beverages.